2021
DOI: 10.4103/jcecho.jcecho_61_21
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging for Atrial Fibrosis Detection in the Era of Precision Medicine

Abstract: In recent years, atrial fibrillation (AF) has increasingly become a focus of attention because it represents the most encountered arrhythmia in clinical practice and a major cause of morbidity and mortality. Issues underlying AF have long been debated; nevertheless, electrical, contractile, and structural remodeling is demonstrated to be the pivotal contributor to arrhythmic substrate. Fibrosis is a hallmark of arrhythmogenic structural remodeling, resulting from an accumulation of fibrillar collagen deposits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…In the present study, we found a significant difference between the patients that successfully blocked the CSD-LA musculature (Group A) and those who did not (Group B) in the acute AF induction rate (53.2% vs. 83.3%, p = 0.013) and atrial arrhythmia recurrences of follow-up (25.5% vs. 50.0%, p = 0.039). These results might add further clinical evidences for the associations of the CS distal musculature with acute AF induction and its role in improving the outcomes of PersAF during follow up, which were coincident with previous studies conducted by Barletta et al and Huang et al ( 6 , 8 ). Among the patients of Group A, the results of ROC curve analysis suggested that under the premise of blocking CSD-LA, LVA of LA below 19% was paralleled with lower acute AF induction (sensitivity and specificity of 92.3 and 90.5%) and LVA of LA below 19.6% accounted for a lower rate of atrial arrhythmia recurrences (sensitivity and specificity of 100 and 65.7%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we found a significant difference between the patients that successfully blocked the CSD-LA musculature (Group A) and those who did not (Group B) in the acute AF induction rate (53.2% vs. 83.3%, p = 0.013) and atrial arrhythmia recurrences of follow-up (25.5% vs. 50.0%, p = 0.039). These results might add further clinical evidences for the associations of the CS distal musculature with acute AF induction and its role in improving the outcomes of PersAF during follow up, which were coincident with previous studies conducted by Barletta et al and Huang et al ( 6 , 8 ). Among the patients of Group A, the results of ROC curve analysis suggested that under the premise of blocking CSD-LA, LVA of LA below 19% was paralleled with lower acute AF induction (sensitivity and specificity of 92.3 and 90.5%) and LVA of LA below 19.6% accounted for a lower rate of atrial arrhythmia recurrences (sensitivity and specificity of 100 and 65.7%).…”
Section: Discussionsupporting
confidence: 91%
“…This approach has also presented a similar result in the DECAAF study. Additionally, the Bipolar mapping is a convenient, efficient, and alternative way to quantify the fibrotic area of the LA (6). Besides, the CS Abbreviations: PersAF, Persistent atrial fibrillation; CS, coronary sinus; AFL, atrial flutter; AF, fibrillation; CSD, distal coronary sinus; LA, left atrial; LVA, low voltage area; CPVI, circumferential pulmonary vein isolation; SR, sinus rhythm; PVs, pulmonary veins; PAF, paroxysmal atrial fibrillation; AT, atrial tachycardia; EC, electrical cardioversion; AI, ablation index; TPI, tissue proximity indication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional transesophageal echocardiography (TOE). LA diameter, area and volume help quantify LA anatomical remodeling, and are used as predictors of AF onset and recurrence [ 19 ]. The LA is also a marker of diastolic dysfunction and increased LA pressures, both associated with the development of AF [ 20 , 21 ].…”
Section: Left Atrial Size In Afmentioning
confidence: 99%
“…Nevertheless, AF recurrence after ablation is highly correlated with previous atrial remodeling [5]. Atrial fibrosis can possibly be estimated via an electroanatomic mapping (EAM) system [6], combining electrophysiological data with anatomical information for the construction of 3D endocardial maps [7,8], thereby becoming an essential tool to assess the underlying substrate for the presence of low-voltage areas (LVAs) at the time of the ablation [9]. LVAs have been described both in paroxysmal and persistent AF, hypothesizing that LVAs are not necessarily related to AF duration [10].…”
Section: Introductionmentioning
confidence: 99%